Acute Stroke With Large Ischemic Core Treated by Thrombectomy: Predictors of Good Outcome and Mortality. Issue 5 (May 2019) - Panni, Pietro; Gory, Benjamin; Xie, Yu; Consoli, Arturo; Desilles, Jean-Philippe; Mazighi, Mikael; Labreuche, Julien; Piotin, Michel; Turjman, Francis; Eker, Omer Faruk; Bracard, Serge; Anxionnat, René; et al.
Abstract : Background and Purpose—: Acute stroke patients with a large ischemic core may still benefit from mechanical thrombectomy (MT), but the predictors of clinical outcome are not well known after MT. We investigated the clinical and imaging factors associated with good outcome and mortality at 90 days in acute stroke patients with a large baseline ischemic core treated with MT. Methods—: Data from the multicentric prospective ETIS (Endovascular Treatment in Ischemic Stroke) registry of consecutive acute ischemic stroke patients treated with MT from January 1, 2012, to August 31, 2016, were retrospectively analyzed. Baseline large ischemic core was defined as diffusion-weighted imaging (DWI)–Alberta Stroke Program Early CT Score of ⩽5. The degree of disability was assessed by the modified Rankin Scale at 90 days. Outcomes included good outcome (modified Rankin Scale score of ⩽2), and mortality (modified Rankin Scale score of 6). Results—: Among 216 patients with DWI-Alberta Stroke Program Early CT Score of ⩽5 (median DWI volume 77 mL, interquartile range 52–120 mL) treated with MT, good outcome was achieved in 55 (25.4%) patients and 75 (34.7%) died at 90 days. Hemorrhagic transformation was detected in 40 (18.5%) patients within 24 hours post-MT. Older age (adjusted odds ratio [OR] for every 10 years, 0.62; 95% CI, 0.48–0.80; P <0.001) and increased DWI lesional volume (adjusted OR, 0.98; 95% CI, 0.97–0.99; P <0.001) were associated with a lower chance of achieving a good outcome, while successful recanalization (modified Thrombolysis in Cerebral Infarction [mTICI] grades of ⩽2b) predicted good outcome (adjusted OR, 4.56; 95% CI, 1.79–11.62; P =0.001). Successful recanalization (OR, 0.46; 95% CI, 0.22–0.97; P =0.042), increased DWI lesional volume (OR, 1.02; 95% CI, 1.01–1.03; P <0.001), age (OR for every 10 years, 1.72; 95% CI, 1.31–2.26; P <0.001), and diabetes mellitus (OR, 3.23; 95% CI, 1.34–7.8; P =0.009) were independent predictors of 90-day mortality. Conclusions—: Successful recanalization and baseline DWI lesional volume are the strongest predictors of outcome in stroke patients with a large ischemic core. Abstract : Supplemental Digital Content is available in the text.